PENGELOLAAN ARSIP DINAMIS INAKTIF PADA KANTOR DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN PUNCAK JAYA - Lood, Nusmince; Suryaningtyas, Dianawati; Mariani Manik, Yuni (Jurnal Riset Mahasiswa Manajemen, 2025)
The management of dynamic inactive archive was done in order to make the archive become reusable when necessary, such as in decision-making or in other activities related to such archives. The archive was reusable when it was in a good condition and provided well-preserved information therein. The objectives of this study were to know how was the management of dynamic inactive archives, what are the obstacles that is facing during the implementation of the management of dynamic inactive archives, and also the solutions that were conducted to solve the obstacles during the management of dynamic inactive archives at the Regional Archive and Library Office of Puncak Jaya Regency. The informants of this study were the Head Office, the Head of Management and Service Archive Section, the Archivist, the Staff, and the Archive Users. The technique of collecting data was conducted through observation, interview, and documentation. The data analysis was done through reducing data, doing presentation, and drawing conclusion. The result of the study of management of dynamic inactive archive was started from arranging and saving the archives through the process of sorting, bundling, describing, classifying, packaging, assessing, drawing up description card, maneuver card, and maneuver archive, drawing up the archives into boxes, drawing up the boxes into archive shelves and drawing up the list of details archives order (DPA), maintaining and securing the archives by cleaning it and preventing any damages by using chemical substances, controlling the archive borrowing, and destroying the archives which have been expired. The obstacles during the implementation were the lack of human resources, unidentified archives, infrastructures which lack of support, and non standard saving rooms. The solutions that were done by the Regional Archive and Library Office were by hiring outsourcing employers, conducting some trainings to governmental institutions at Puncak Jaya regency, and asking for extra infrastructure for regional archives. The conclusion based on this research was that the archive management was considered well done in accordance with the procedures starting from the process of saving up to decimating the archives. The obstacles during the implementation were the lack of human resources, unidentified archives, infrastructures which lack of support, and non standard saving rooms. The solutions that were done were hiring outsourcing employers, conducting some trainings, and asking for extra infrastructure. It is suggested that the Regional Archive and Library Office should held a selection of outsourcing employers in accordance with its prequirement, regularly monitor the archive makers unit, and maximaze the infrastructure over there.